Hydrological implications of stable isotope determinants in U.K. waters - Brown, H; Brown, Heather (1984)
The stable isotopes of oxygen and hydrogen have been employed worldwide as natural hydrological tracers, and most successfully in areas where extremes of climatic seasonality or relief exist. This project aims to assess the viability of the stable isotope technique for studies in the U.K. Systematic sampling was undertaken over two years in the Malham (Carboniferous limestone) and Lambourn (Chalk) areas. The monthly isotopic input signal in precipitation was found to be clearly definable, but less strongly seasonal than found elsewhere. Larger isotopic variations were revealed in weekly and within-storm samples. Snowmelt appeared to provide the most reliable 'spike' for tracing purposes. An attempt to relate weekly precipitation δ180 values to air mass characteristics was encouraging for further investigations. Variations of isotope signal with altitude were erratic and not in accordance with normally accepted relationships. Isotopic variations in groundwaters of both areas, and in surface waters of the Lambourn area, rarely exceeded measurement error, and were close to mean annual values in precipitation. This indicated complete mixing of the input waters over one year or more. The isotopic range in precipitation was reduced by ~60% in surface waters of the Malham area. Early mixing and storage of water in the soil and/or upper karstic zone were indicated by comparison of the isotope data with conventional hydrological measurements at resurgences, and supported by strong signal attenuation measured in soil moisture. At certain sites, isotopic evidence revealed a persistence of winter recharge into summer baseflow. A smooth and strongly seasonal isotope signal, discovered in the waters of Malham Tarn, was attributed to evaporation processes and suggests important practical uses. It is concluded that the general application of the stable isotope technique may be more restricted in the U.K. than elsewhere, but that its provision of a new dimension to conventional data should contribute significantly in the future to selected hydrological studies.